Self-Powered Temperature Sensor with Seebeck Effect Transduction for Photothermal-Thermoelectric Coupled Immunoassay - Huang, Lingting; Chen, Jialun; Yu, Zhonghua; Tang, Dianping (Analytical chemistry (Washington), 2020)
A self-powered temperature sensor based on Seebeck effect transduction was designed for photothermal-thermoelectric coupled immunoassay of α-fetoprotein (AFP). In this system, glucose oxidase (GOx)-conjugated detection antibody was first captured onto the microplate by target-induced sandwich-type immunoreaction. Thereafter, the as-generated hydrogen peroxide via the GOx-glucose system oxidized 3,3',5,5'-tetrametylbenzidine (TMB) into photothermal product oxidized TMB (ox-TMB). Under near-infrared (NIR) laser irradiation, the temperature change of ox-TMB was read out in an electrical signal by the flexible thermoelectric module in a 3D-printed integrated detection device. Under optimal conditions, the photothermal-thermoelectric coupled immunoassay exhibited a limit of detection of 0.39 ng mL AFP over a dynamic linear range from 0.5 to 60 ng mL . Impressively, such a strategy presented herein offers tremendous potentials for applying many other high-efficiency thermoelectric materials in ultrasensitive biosensors.